The Analysis of Adverb of Manner Found in the Novel “Harry Potter” - Emi Mura Isu; I Made Juliarta (Universitas Bali Dwipa, 2026)
This study aims to identify and analyze the syntactic structure of adverbs of manner found in J.K. Rowling’s novel, Harry Potter and the Sorcerer’s Stone. The primary purpose is to categorize the types of adverbs of manner used and to illustratetheir structural positions within sentences using tree diagram representations. The data source for this qualitativeresearch is the first volume of the Harry Potter series, from which a purposive sample of 150 sentences containing adverbs of manner was extracted. The research method employed is a descriptive-qualitative approach involving data reduction,data display, and conclusion drawing. Results indicate that adverbs of manner in the novel predominantly function asadjuncts within Verb Phrases (VP). Furthermore, the analysis reveals that most adverbs are formed throughsuffixation (-ly) and occupy various positions, though post-verbal positioning is most frequent. The findings suggest that J.K. Rowling uses descriptive adverbs to enhance the vividness of character actions. These interpretations providepedagogical applications for linguistics students in understanding syntactic hierarchies and the functional role of adverbs innarrative literature, offering a practical model for tree diagram construction in English syntax studies.